Intra-host SARS-CoV-2 single-nucleotide variants emerged during the early stage of COVID-19 pandemic forecast population fixing mutations. Issue 5 (May 2022) - Zhang, Yi; Jiang, Ning; Qi, Weiqiang; Li, Tao; Zhang, Yumeng; Zhang, Haocheng; Wu, Jing; Zhu, Zhaoqin; Ai, Jingwen; Qiu, Chao; Zhang, Wenhong
Highlights: A large proportion of iSNVs could be found in the several dominant VOCs in early-stage samples. iSNVs located spike protein may help in immune escape forecasting. The dominant C-U/G-A in iSNVs indicate APOBEC driven SARS-CoV-2 to adaptation.